The effect of perception on consumers' attitude towards purchasing Islamic Banking products - Lo, Bryan Ching Wing (Universiti Malaysia Sabah, 2015)
Islamic banking concept is highly regulated by emphasizing Shariah principles which is conventional banking does not apply in daily banking transaction. Islamic banking could be defined as a banking system that is based on the principle of Islamic law and guided by Islamic economics which focus on sharing profit and loss with the prohibition of the collection and payment of interest. The problem statement of this study can be divided into industrial problems and academic problems that connected to the gap of the study. The primary objective of this research is to examine the relationship between consumer perception and consumer purchase intention and evaluate the underlying determinants that influence consumer intention to consumer Islamic banking with the aim of developing a behavioral framework for analyzing and explaining consumer behavior regarding Islamic banking. This research has been undertaken using mixed method which incorporates aspects of qualitative and quantitative research both. This is selected because survey strategy provides different options of data collection such as; interviews, questionnaire and focus group. The sample size used in this research will be 600 customers of any of the listed Islamic bank in Malaysia. To be on the safe side, 620 respondents were approached and to eliminate the error of responses, the additional survey will be evaluated. Since, information for this research is gathered both qualitatively and quantitatively, consequently it is important to select suitable techniques for data analysis to viably translate the outcome in an understandable manner and achieve the finished conclusion. The researcher has performed appropriate data analysis techniques to examine the values such as Beta, chi square, sig value, standard error and t value. Moreover, the study likewise performed reliability test to access of the obtained data is reliable to use. The research is concluded that comprehensively covers the aspect of Islamic banking and its role on the minds of the customer. Furthermore, results also concluded that consumer intent to purchase Islamic banking products were significantly influenced by the certain factors that shaped their behaviour and perception of an Islamic banking product. Additionally, statistically strong relationship between the dependent variable i.e. intent to purchase and all four independent variables including attitude, consumer perception, perceived control behaviour and subjective norm confirmed the perception of consumers regarding Islamic banking and the way if influenced the their purchase intention.